1988
DOI: 10.1002/1097-0142(19880501)61:9<1889::aid-cncr2820610928>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of cryosurgery in the treatment of primary liver cancer Report of 60 Cases

Abstract: Of 60 patients, subclinical stage amounted to 35% (21/60), moderate stage 55% (33/60) and late stage 10% (6/60). There were 21 cases with small PLC (15 cm). The postoperative course was uneventful in all of the 60 patients. These was no operative mortality, and there was no complications such as rupture of tumor, secondary bleeding, bile leakage, or abdominal infection. The 1-year, 2-year, 3-year, 4-year, and 5-year survival rates were 51.7% (30/58), 33.9% (19/56), 20.8% (11/53), 15.6% (7/45), and 11.4% (5/44)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
4

Year Published

1989
1989
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(53 citation statements)
references
References 11 publications
0
49
0
4
Order By: Relevance
“…It was 10 months (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in patients without reresection calculated from the time of diagnosis to recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…It was 10 months (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] in patients without reresection calculated from the time of diagnosis to recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…During the last 10 years cryotherapy has gained importance especially for treatment of nonresectable primary and secondary liver tumors [2] and for transperineal ablation of the prostate in patients with adenocarcinoma of the prostate [3][4][5][6][7][8]. Cryoablation of the prostate has been reported to be a safe procedure with promising results following cryoablation of prostate cancers with significant tumor marker responses [5,7,8] and 79% to 90% negative biopsy results after 3 to 12 months [5][6][7][8].Hepatic cryotherapy has been shown to be effective for treating colorectal liver metastases [9 -16] and hepatoma [17][18][19]. Results on more than 800 patients have been reported [2] with median survival times of 26 months following cryotherapy of nonresectable colorectal liver metastases [12, 13] and 5-year survival rates of 11.4% to 64.2% [17,18] following cryoablation of hepatoma.…”
mentioning
confidence: 99%
“…Results on more than 800 patients have been reported [2] with median survival times of 26 months following cryotherapy of nonresectable colorectal liver metastases [12,13] and 5-year survival rates of 11.4% to 64.2% [17,18] following cryoablation of hepatoma.…”
mentioning
confidence: 99%
“…The temperature of the treated area falls to as low as -190°C. Tumour eradication is seen and survival times for otherwise untreatable tumours increased (Ravikumar et al, 1987;Zhou et al, 1988). External radiotherapy to the liver is limited by the problem of toxicity (Sherman et al, 1978) but the interstitial implantation of radioactive seeds has been reported (Dritchilo et al, 1986).…”
Section: )mentioning
confidence: 99%